Dipeptidyl Peptidase 1 Inhibitor AZD7986 Induces a Sustained, Exposure‐Dependent Reduction in Neutrophil Elastase Activity in Healthy Subjects. Issue 6 (16th April 2018) - Palmér, Robert; Mäenpää, Jukka; Jauhiainen, Alexandra; Larsson, Bengt; Mo, John; Russell, Muir; Root, James; Prothon, Susanne; Chialda, Ligia; Forte, Pablo; Egelrud, Torbjörn; Stenvall, Kristina; et al.
Abstract : Neutrophil serine proteases (NSPs), such as neutrophil elastase (NE), are activated by dipeptidyl peptidase 1 (DPP1) during neutrophil maturation. High NSP levels can be detrimental, particularly in lung tissue, and inhibition of NSPs is therefore an interesting therapeutic opportunity in multiple lung diseases, including chronic obstructive pulmonary disease (COPD) and bronchiectasis. We conducted a randomized, placebo‐controlled, first‐in‐human study to assess the safety, tolerability, pharmacokinetics, and pharmacodynamics of single and multiple oral doses of the DPP1 inhibitor AZD7986 in healthy subjects. Pharmacokinetic and pharmacodynamic data were analyzed using nonlinear mixed effects modeling and showed that AZD7986 inhibits whole blood NE activity in an exposure‐dependent, indirect manner—consistent with in vitro and preclinical predictions. Several dose‐dependent, possibly DPP1‐related, nonserious skin findings were observed, but these were not considered to prevent further clinical development. Overall, the study results provided confidence to progress AZD7986 to phase II and supported selection of a clinically relevant dose.